2017
DOI: 10.5578/khj.25233
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Electrical and Electromechanical Characteristics in Patients with Rheumatic Mitral Stenosis

Abstract: Introduction: AF in patients with mitral stenosis (MS) causes significant morbidity and mortality. PMBV, which is a treatment of choice for patients with MS, is a highly successful procedure that provides significant improvement in symptoms and echocardiographic parameters. In this study we aimed to demonstrate the probable effects of PMBV on novel echocardiographic and electrocardiographic parameters that can predict the development of AF in 1-year period in patients with MS. Patients and Methods:Twenty-eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In accordance with those studies, we found a significantly higher PWD for patients with MS than for control subjects, and it was correlated with the echocardiographic parameters of MS significance. We also found that P max and PWD significantly decreased within 72 h after PMBV as previously described by other studies (13)(14)(15) . Demirkan et al have shown in a study including 30 patients with moderate and severe MS that there is a statistically significant decrease in atrial electromechanical delay with P max and PWD in the early period after PMBV (in 72 h) (13) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In accordance with those studies, we found a significantly higher PWD for patients with MS than for control subjects, and it was correlated with the echocardiographic parameters of MS significance. We also found that P max and PWD significantly decreased within 72 h after PMBV as previously described by other studies (13)(14)(15) . Demirkan et al have shown in a study including 30 patients with moderate and severe MS that there is a statistically significant decrease in atrial electromechanical delay with P max and PWD in the early period after PMBV (in 72 h) (13) .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that PWD is increased in patients with rheumatic MS (4,5,13,14) . Turhan et al showed a decrease in Pmax and PWD in both short and long terms after PMBV (4) .…”
Section: Discussionmentioning
confidence: 91%